Face masks for community use: An awareness call to the differences in materials. Issue 8 (6th July 2020) - Sousa‐Pinto, Bernardo; Fonte, Ana Paula; Lopes, Antónia Andrade; Oliveira, Bruno; Fonseca, João Almeida; Costa‐Pereira, Altamiro; Correia, Osvaldo
Abstract : See related Reply See related Reply